1988
DOI: 10.1002/jlcr.2580250213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [14C]propane

Abstract: [14C]propane of high chemical and radiochemical purity has been prepared from [14C]acetone via [1,3‐14C]acetone semicarbazone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…82 Studies in which n-hexane and n-heptane were converted over H-ZSM-5 at 683 K resulted in the production of C 1 −C 5 aliphatics as well as a significant yield of C 7 and C 8 aromatics (over 25 wt % for both reactants). 83 The presence of aliphatics smaller than the reactant indicates that alkane cracking is occurring simultaneously with cyclization reactions. The formation of aromatics larger than the reactant show that side reactions of cyclization, such as olefin oligomerization and alkylation of aromatics, also occur.…”
Section: Acs Catalysismentioning
confidence: 99%
“…82 Studies in which n-hexane and n-heptane were converted over H-ZSM-5 at 683 K resulted in the production of C 1 −C 5 aliphatics as well as a significant yield of C 7 and C 8 aromatics (over 25 wt % for both reactants). 83 The presence of aliphatics smaller than the reactant indicates that alkane cracking is occurring simultaneously with cyclization reactions. The formation of aromatics larger than the reactant show that side reactions of cyclization, such as olefin oligomerization and alkylation of aromatics, also occur.…”
Section: Acs Catalysismentioning
confidence: 99%
“…Considering strong acidity of the Brønsted acid sites in the zeolite, a mechanism based on carbenium ion chemistry has been suggested. Experimental investigations involving model reactants , have concluded that (i) dienes or trienes are the precursor for cyclization, (ii) napthenes like cyclohexane are unlikely to be the intermediates for cyclization on monofunctional Brønsted acid zeolites, and (iii) ring closure to cyclic olefins is irreversible. These studies concluded that ring closure is less activated than other important reactions like dehydrogenation and cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Monofunctional acid catalysts exhibit relatively low aromatics yields which is due to preferentially high cracking, isomerization, and β-scission reactivity. [6][7][8][9][10] Bifunctional metal/ H-ZSM-5 catalysts using Ga, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Zn, [27][28][29][30][31][32][33][34] and Pt 10,7,[35][36][37][38][39][40] dramatically improve aromatics yields but are prone to deactivation via coking 31 and, although better than purely acidic catalysts, are nevertheless limited in both aromatics yield and selectivity toward H 2 versus CH 4 byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatization of even single component feedstocks is complex, involving a large number reaction steps, many of which are not well understood or are only postulated. However, it is generally agreed that the relevant reactions for conversion of light alkanes to aromatics consists of (1) alkane C-H activation to alkoxide/carbenium complexes, (2) dehydrogenation to olefins, (3) oligomerization to higher olefins, (4) rapid isomerization, (5) β-scission, (6) cyclization, and (7) dehydrogenative aromatization. 10,41 Cyclizations involving C(6+) olefins are believed to occur via carbocation/alkoxide-based pathways relatively independent of oligomerization.…”
Section: Introductionmentioning
confidence: 99%